2011
DOI: 10.1002/cjg2.1614
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Anisotropy of Upper Mantle Beneath the Ordos Block and Adjacent Regions

Abstract: Based on the polarization analysis of teleseismic SKS waveform data recorded at 90 broadband stations in the Ordos block and adjacent regions, the splitting parameters of fast polarization direction and delay time between the fast and slow shear waves are determined for each station using the minimum transverse energy method, yielding the images of upper mantle anisotropy. Combined with the GPS horizontal velocity field with respect to the Ordos block during 1999~2007, we analyze the seismic anisotropy as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…Tian & Santosh, 2015), the asthenosphere (X. Y. Yang et al, 2019) or both (P. Wu, Wang, et al, 2012). In our study, the Vp azimuthal anisotropy is mainly attributed to the LPO due to the thermal flow or the stress.…”
Section: Azimuthal Anisotropymentioning
confidence: 47%
See 1 more Smart Citation
“…Tian & Santosh, 2015), the asthenosphere (X. Y. Yang et al, 2019) or both (P. Wu, Wang, et al, 2012). In our study, the Vp azimuthal anisotropy is mainly attributed to the LPO due to the thermal flow or the stress.…”
Section: Azimuthal Anisotropymentioning
confidence: 47%
“…Figure 14c shows that the FVDs of the P ‐wave and the S ‐wave are almost orthotropic. The previous studies suggested that the anisotropy estimated from shear‐wave splitting measurements may originate from the lithosphere (X. Tian & Santosh, 2015), the asthenosphere (X. Y. Yang et al., 2019) or both (P. Wu, Wang, et al., 2012). In our study, the Vp azimuthal anisotropy is mainly attributed to the LPO due to the thermal flow or the stress.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there has to be YU ET AL. (Chang et al, 2011(Chang et al, , 2016Hu et al, 2011;Huang et al, 2008;León Soto et al, 2012;J. Li et al, 2011;Y.…”
Section: Discussionmentioning
confidence: 99%
“…(a) shows the average P-wave velocity perturbations from 150 to 250 km. Red bars represent fast-polarization directions and splitting delay times of previous SKS-splitting analyses(Chang et al, 2011(Chang et al, , 2016Hu et al, 2011;Huang et al, 2008;León Soto et al, 2012;J. Li et al, 2011;Y.…”
mentioning
confidence: 99%
“…These earthquakes are all distributed in the Ordos surrounding fault zone and faulted basin, but no earthquakes of Ms6.0 or above have ever occurred in the Ordos Basin. Previous studies have focused on crustal deformation, velocity structure, electrical mechanism, deep thermal structure and crustal stress field in the Ordos Block [3][4][5][6][7][8][9][10][11][12][13], these research results have laid a good theoretical foundation and provided sufficient reference for this study.…”
Section: Introductionmentioning
confidence: 99%